Inclusive Educational Spaces and Social Pedagogical Recognition: Interaction- and Social-Pedagogy-Inspired Analysis of Space Dynamics in Compulsory, Upper-Secondary and Post-Secondary Education - Goran Basic; Galina Vasylivna Lokareva; Nadiya Vasylivna Stadnichenko (MDPI AG, 2021)
The purpose of this article is to provide a new understanding of the essence of inclusive educational spaces as a pedagogical phenomenon that presents different scientific approaches to the concept of educational space, and the importance of interpersonal interactions in educational spaces, and also presents the authors' interpretations of their essence. The analytical basis is a literature review of various studies from the domains of symbolic interactionism, social constructivism, ethnomethodology, the sociology of knowledge, education, pedagogy and social pedagogy. Empirical sequences in the reviewed literature that exemplify inclusive educational spaces are derived from the organisational and practical work of compulsory and upper-secondary schools related to newly arrived students and students who use alcohol and narcotics, and from the context of the organisational and practical work of universities related to the education of future actors. The importance of recognizing the role of creative educational spaces as a leading requirement for the preparation of students for future communicative interactions in professional communication is revealed, and the structural characteristics of these spaces' content and functional load are provided. Inclusive educational spaces and professionals' inclusive approach demand that schools practically and collaboratively organise work with students in the educational space, show support for them and give them room to manoeuvre to ensure that professional actors in the school and university thrive in their practical work with students, both in relation to the expected normative right and deviant acting in the educational space and in relation to laws and governing documents that, to a certain extent, govern practical work in these educational spaces. The study contributes to the development of knowledge regarding (1) dealing with social interaction and inclusive educational spaces combining (a) the experiences of students in educational space, (b) the experiences of professional actors in educational space, and (c) the development of integration and social pedagogical recognition in educational space; (2) the significance of these social interactions and inclusive educational spaces in the creation and recreation of students' and professionals' identities; and (3) alternative social pedagogical approaches to analysing inclusive educational spaces in compulsory, upper-secondary and post-secondary education.